2016
DOI: 10.1590/1980-5373-mr-2015-0241
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Titanium Nitride Thin Films Deposited on Silicon by Plasma Discharge Technique in Cathodic Cage

Abstract: Titanium nitride films were deposited on silicon by plasma discharge in cathodic cage with holes and without holes on the sides. Each film was deposited with a pressure of 253 Pa, treatment time of 2 h, and at diverse conditions of temperature and gas flow of N 2 and H 2 . The electrochemical polarization and electrochemical impedance techniques were used to understand the effect on the electrochemical properties of these films in relation to the presence or absence of holes on the sides of the cathodic cage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Aiming to prevent such issues, liquid lubricants have been extensively used. Nevertheless, usual inefficiency in vacuum situations and environmental aggressiveness have encouraged researches towards their reduction or elimination [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to prevent such issues, liquid lubricants have been extensively used. Nevertheless, usual inefficiency in vacuum situations and environmental aggressiveness have encouraged researches towards their reduction or elimination [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the phases of deposited film can be controlled by treatment parameters. In 2016, Bottoni et al [68] used CCPD to deposit titanium nitride film on silicon and evaluated its electrochemical behavior. They found the dominant role of temperature, gasses admixture, and holes on the sides of the cathodic cage.…”
Section: Ccpd For Titanium Nitride Synthesismentioning
confidence: 99%